2016
DOI: 10.1158/1535-7163.mct-16-0157
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Susceptibility to Emactuzumab (RG7155) Treatment

Abstract: Blockade of colony-stimulating factor-1 receptor (CSF-1R) enables the therapeutic targeting of tumor-associated macrophages (TAM) in cancer patients. Various CSF-1R inhibitors, mAbs, and tyrosine kinase inhibitors are currently evaluated in early clinical trials. Presence of an alternative survival signal, such as GM-CSF, rescues human monocyte-derived macrophages from CSF-1R inhibitor-induced apoptosis. In this study, we sought to identify additional factors that mediate resistance to CSF-1R-blocking antibody… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 46 publications
2
60
0
Order By: Relevance
“…For both strategies, the choice of an appropriate combination partner will be key to reprogramming a tumor-promoting TME or boosting a pre-existing anti-tumor immune response. Recently, in vitro-differentiated CD206-expressing human macrophages were shown to be rescued from emactuzumab-induced depletion in the presence of IL-4 [50], demonstrating the importance of the local cytokine micromilieu. As CD206 expression is high on alveolar macrophages, an elevated concentration of IL-4 in lung cancer patients may result in resistance to CSF1R inhibitors.…”
Section: Local Tissue Macrophage and Disease Specificity Impacting Csmentioning
confidence: 99%
“…For both strategies, the choice of an appropriate combination partner will be key to reprogramming a tumor-promoting TME or boosting a pre-existing anti-tumor immune response. Recently, in vitro-differentiated CD206-expressing human macrophages were shown to be rescued from emactuzumab-induced depletion in the presence of IL-4 [50], demonstrating the importance of the local cytokine micromilieu. As CD206 expression is high on alveolar macrophages, an elevated concentration of IL-4 in lung cancer patients may result in resistance to CSF1R inhibitors.…”
Section: Local Tissue Macrophage and Disease Specificity Impacting Csmentioning
confidence: 99%
“…Documenting patients’ genetic profile and the corresponding therapeutic outcome are also beneficial in correlation studies to better predict patient response as well as in refining drug development. In the case of CSF-1R inhibition therapy, certain single nucleotide polymorphisms (SNPs) in CSF-1R have been identified that reduce the potency of emactuzumab [226]. Nonetheless, the study may help in the future design of the next-generation CSF-1R blockade therapy.…”
Section: Perspectives On Tam-targeted Therapeuticsmentioning
confidence: 99%
“…CSF1-deficient mice showed a 50% decrease in macrophage infiltration while neutrophil infiltration was increased during tumor progression in a mouse model of pancreatic islet cancer (55). mAbs and small molecules targeting CSF1 (mAb anti-CSF1) or CSF1-R (BLZ945, emactuzumab, PLX3397) were subjected to numerous studies and were shown to deplete macrophages in a tissue-specific manner (56, 57). Overall, CSF1-R inhibitors deplete TAMs and abolish tumor growth, angiogenesis, and metastasis.…”
Section: Targeting Tams With Chemotherapy or Immunotherapymentioning
confidence: 99%